Osmotic and Specific Ion Effects on the Germination of Prosopis strombulifera - SOSA, LAURA (Ann Bot, 2005)
• Background and Aims Salinity can affect germination of seeds either by creating osmotic potentials that prevent water uptake or by toxic effects of specific ions. Most studies have only used monosaline solutions, although these limit the extent to which one can interpret the results or relate them to field conditions. The aim of this work was to evaluate the germination of Prosopis strombulifera seeds under increasing salinity by using the most abundant salts in central Argentina in monosaline or bisaline iso-osmotic solutions, or in solutions of mannitol and polyethylene glycol. • Methods Seeds were allowed to germinate under controlled conditions in a germination chamber at 30 ± 1 °C and at 80 % r.h. Salinizing agents were KCl, NaCl, Na(2)SO(4), K(2)SO(4), NaCl + Na(2)SO(4) and KCl + K(2)SO(4) and osmotic agents were polyethylene glycol 6000 and mannitol. Treatments for all osmotica consisted of 0·0, −0·4, −0·8, −1·2, −1·5, −1·9 and −2·2 MPa solutions. • Key Results The percentage of germination decreased as salinity increased. [Formula: see text] in monosaline solutions, with osmotic potentials −1·2 MPa and lower, was more inhibitory than Cl(−) at iso-osmotic concentrations. This [Formula: see text] toxicity was alleviated in salt mixtures and was more noticeable in higher concentrations. K(+) was more inhibitory than Na(+) independently of the accompanying anion. • Conclusions Different responses to different compositions of iso-osmotic salt solutions and to both osmotic agents indicate specific ionic effects. This study demonstrates that the germination of P. strombulifera is strongly influenced by the nature of the ions in the salt solutions and their interactions. Comparative studies of Cl(−) and [Formula: see text] effects and the interaction between [Formula: see text] and Cl(−) in salt mixtures indicate that extrapolation of results obtained with monosaline solutions in the laboratory to field conditions can be speculative.